Knowledge and attitudes about research ethics among social researchers in Vietnam: A cross-sectional study - Kham Van Tran; Cuong Huy Pham; Nam Thanh Tran; Lan Thi Thai Nguyen; Nhung Thi Kim Nguyen (Institute of Advanced Engineering and Science, 2022)
Social research has attracted significant attention in Vietnam during recent years with more questions and discussions about how to promote the research outputs and publications in this area. However, there is limited information about the knowledge and attitudes of social researchers for research ethics in Vietnam. This paper aims to assess the knowledge and attitudes of social researchers about research ethics in Vietnam. A survey with 1200 questionnaires, through convenience sampling, was sent either printed copies or email to social researchers in the universities and research institutions in Vietnam. Our response rate was 65% (782), with mean age: 35.9 years (sd=.307). The results show that around one fifth had been trained with research ethics (23.5%), which led to significant responses to the